Components of ambient air pollution affect thrombin generation in healthy humans: the RAPTES project. Issue 5 (1st February 2013) - Strak, Maciej; Hoek, Gerard; Steenhof, Maaike; Kilinc, Evren; Godri, Krystal J; Gosens, Ilse; Mudway, Ian S; van Oerle, René; Spronk, Henri M H; Cassee, Flemming R; Kelly, Frank J; Harrison, Roy M; et al.
Abstract : Objectives: Increases in ambient particulate matter (PM) have been associated with an elevated risk of stroke, myocardial ischaemia and coronary heart disease, with activation of blood coagulation likely playing an important role. PM-mediated activation of two major activation pathways of coagulation provides a potential mechanism for the observed association between PM and cardiovascular disease. However, it remains unclear which specific characteristics and components of air pollution are responsible. Methods: In order to investigate those characteristics and components, we semiexperimentally exposed healthy adult volunteers at five different locations with increased contrasts and reduced correlations among PM characteristics. Volunteers were exposed for 5 h, exercising intermittently, 3–7 times at different sites from March to October 2009. On site, we measured PM mass and number concentration, its oxidative potential (OP), content of elemental/organic carbon, trace metals, sulphate, nitrate and gaseous pollutants (ozone, nitrogen oxides). Before and 2 and 18 h after exposure we sampled blood from the participants and measured thrombin generation using the calibrated automated thrombogram. Results: We found that thrombin generation increases in the intrinsic (FXII-mediated) blood coagulation pathway in relation to ambient air pollution exposure. The associations with NO2, nitrate and sulphate were consistent and robust, insensitive to adjustment for other pollutants. The associations with tissue factor-mediated thrombogenicity were not very consistent. Conclusions: Ex vivo thrombin generation was associated with exposure to NO2, nitrate and sulphate, but not PM mass, PM OP or other measured air pollutants.